l-Phenylalanine Ammonia-lyase (Maize): Partial Purification and Response to Gibberellic Acid and Cycloheximide of l-Phenylalanine and l-Tyrosine Ammonia-lyase Activities - Reid, Philip D. (1972)
Extracts of maize leaf sheath tissue deaminate both l-phenylalanine and l-tyrosine. The activities with both substrates are enhanced by treating the plant with gibberellic acid. Both activities decrease rapidly at the same rate when tissue is incubated in a moist atmosphere, and this decrease can be slowed by treatment with cycloheximide. The ratio of the activities was constant throughout a series of purification steps which included acetone and ammonium sulfate precipitation, and passage through an agarose column. The two activities could not be separated by isoelectric focusing. These results support our earlier conclusion that both activities occur at the same catalytic site.